IMPLEMENTATION OF CANVA-BASED INTERACTIVE GAMES IN INCREASING STUDENTS' INTEREST IN LEARNING ARABIC AT MTSN 1 MEDAN-NORTH SUMATERA - Fadlan Rawi Nasution; Nayla Khalisa; Arjuna Dwi Maulana; Sakholid Nasution (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
The low interest in learning Arabic is one of the problems in learning Arabic. Interest in learning Arabic has a very important role in supporting the abilities of the four maharah in Arabic. The purpose of this study is to provide a solution to the low interest in learning Arabic of class VII-D MTsn 1 Medan students through the implementation of interactive games based on canva. The research method used in this study is a qualitative method with a descriptive qualitative approach, while data collection techniques use interviews, observations and documentation. The results of the study indicate that the implementation of interactive games based on canva has a very important role in increasing the interest in learning Arabic of class VII-D MTsn 1 Medan students, through the implementation of interactive games based on canva students become more active and enthusiastic in learning Arabic this is shown through the results of observations and interviews with students and Arabic teachers.